Market Structure and Property Rights in Open Source Industries - Michele Boldrin; David K. Levine (Washington University Journal of Law & Policy, 2009)
This Article summarizes briefly the reasons why OS industries should not come as a surprise to economists well trained in traditional competitive theory, and to dissect the economic logic underpinning them. Next it discusses the logical contradictions (or the plain neglect of facts) behind the common misconception that an OS industry is not viable.
Keywords: Open source software; Intellectual property; Digital rights (Intellectual property); Property rights; Software licensing